THE SPACING REQUIREMENT OF COCONUTS ON ATOLLS: RESULTS FROM FOUR SYSTEMATIC SPACING TRIALS IN KIRIBATI - J. J. F. BARR; K. TREWREN (International Coconut Community, 1996)
Four systematic spacing trials were planted between 1969 and 1973 on three islands in the Republic of Kiribati which have contrasting regimes of rainfall, in order to investigate the spacing requirements of coconuts in relation to rainfall (under atoll conditions). Two of the trials are on Kiritimati, which has an annual average rainfall of only 870 mm; one is on Tarawa which receives 2043 mm, and the fourth is on Butaritari which receives 3185 mm. Three of the trials are in the form of an almost complete wheel, whilst the fourth consists off our fan-shaped sectors. The range of planting densities in all trials was from 126 to, 632palms per hectare, in 12 treatments. Due to discontinuity of staff only one of the trials on Kiritimati was recorded during the period in which the coconuts came into, bearing but this showed fairly clearly that there is a relationship between precocity and planting density, with the palms coming into production earlier at the wider spacing. During the period of maximum cropping of the palms the optimum planting density under conditions of 870 mm annual rainfall is outside of the range of densities covered by the trials, and somewhat less than 126 palms per hectare.